PENGARUH KEMAMPUAN KOMPETENSI PAEDAGOGIK GURU TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI SMA IT AL-HIJRAH - Muhammad Khoirul Basyar, Rijal (FKIP UMN ALWASHLIYAH, 2025)
This research aims to obtain information regarding the role of the use of technology-based learning media (ICT) in developing students' social studies learning at the junior high school level. The method used is a heritage study or literature study approach. This research comes from several journals that are relevant to the topic of discussion within the scope of the use of ICT-based learning media in junior high school social studies learning. Data collection was carried out by searching several scientific articles in digital scientific journals and digital websites. Data analysis was carried out using the content method through the process of selecting several scientific articles and scientific sources that were relevant to the scope of the research, so that relevant data was produced. The research results obtained are the use of ICT-based technology as a learning medium in the social studies learning process in junior high schools and relevant media in junior high school social studies learning so that it can increase motivation, learning outcomes and digital literacy in students, especially in the junior high school environment.